2005
DOI: 10.1152/jn.00837.2004
|View full text |Cite
|
Sign up to set email alerts
|

Motor-Unit Activity Differs With Load Type During a Fatiguing Contraction

Abstract: Mottram, Carol J., Jennifer M. Jakobi, John G. Semmler, and Roger M. Enoka. Motor-unit activity differs with load type during a fatiguing contraction. J Neurophysiol 93: [1381][1382][1383][1384][1385][1386][1387][1388][1389][1390][1391][1392] 2005. First published October 13, 2004; doi:10.1152/jn.00837.2004. Despite a similar rate of change in average electromyographic (EMG) activity, previous studies have observed different rates of change in mean arterial pressure, heart rate, perceived exertion, and fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
180
7
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 148 publications
(209 citation statements)
references
References 54 publications
18
180
7
4
Order By: Relevance
“…Given that similar levels of initial tonic excitation have been observed for the force and position tasks by this and previous studies Mottram et al, 2005), the available evidence does not support a change in fusimotor drive during the two tasks. Rather, the increase in reflex responsiveness to heteronymous nerve stimulation during the position task is likely mediated by reduced presynaptic inhibition of Ia afferent terminals.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Given that similar levels of initial tonic excitation have been observed for the force and position tasks by this and previous studies Mottram et al, 2005), the available evidence does not support a change in fusimotor drive during the two tasks. Rather, the increase in reflex responsiveness to heteronymous nerve stimulation during the position task is likely mediated by reduced presynaptic inhibition of Ia afferent terminals.…”
Section: Discussionsupporting
confidence: 63%
“…Subsequent studies have demonstrated that the control strategy used during isometric contractions can alter the recruitment and discharge behavior of single motor units both with (Tax et al, 1989;Tax et al, 1990;Rudroff et al, 2006) and without (Mottram et al, 2005) changes in the distribution of activity among accessory muscles. Furthermore, the duration that sustained (Hunter et al, 2002;Rudroff et al, 2005) and intermittent (Sjogaard et al, 2000) contractions can be maintained before task failure is also influenced by the control strategy used to sustain the task.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been supported by Clark et al (2010Clark et al ( , 2011 who reported that healthy older adults exhibited no reduction in rapid muscle activation characteristics when compared to middle-aged adults. Although it is possible, however, that the limitations associated with surface EMG assessments may not be sensitive enough to elucidate some of these changes detected with intramuscular recordings (Mottram et al 2005;Klass et al 2008). These and previous findings may suggest that the agerelated declines in relative rapid force characteristics may be attributed to factors other than the impairment of rapid muscle activation in healthy older adults.…”
Section: Discussionmentioning
confidence: 82%
“…As motor units activated at the onset of a sustained contraction generally exhibit a decline in discharge rate, a target force is maintained by the progressive recruitment of additional motor units (Bigland-Ritchie et al 1983;Garland et al 1994;Carpentier et al 2001;Mottram et al 2005). The discharge rate of the newly recruited motor units initially increases, but then eventually also declines (Carpentier et al 2001).…”
Section: (C) Neural Adjustments During Sustained Contractionsmentioning
confidence: 99%